Spirit of India - Kalam, APJ Abdul (Delhi Rajpal)
"It looks to me that we need a second vision for the nation, just like the one we had when we were actively pursuing our freedom movement against alien rule. At that time the spirit of nationalism was very strong. This second vision that is needed for making India a developed nation will once again bring the spirit of nationalism to the fore.''
Keywords: Abdul Kalam, A. P. J. (Avul Pakir Jainulabdeen), 1931-2015